Assessment of knowledge, attitude and practice of Pakistani population about the risk factors, causes, complications and management of diabetes mellitus - Muhammad Sajid Hamid Akash; Kanwal Rehman; Komal Jabeen; Fareeha Fiayyaz; Shakila Sabir; Muhammad Ejaz ul Haq (Journal of the Pakistan Medical Association, 2020)
Objective: To compare the knowledge, attitude and practice regarding diabetes mellitus among diabetics and non-diabetics. Methods: The cross-sectional study was conducted at the Government College University, Faisalabad, Pakistan, from December 2017 to April 2018, and comprised subjects recruited randomly from different cities of Punjab, Pakistan. Data was collected using a predesigned structured questionnaire regarding socio-demographic characteristics, general knowledge about diabetes, perception regarding indication, risk factors, diagnosis, and complications, and practices followed for treatment and management of diabetes. Results: Of the 2,000 subjects, 972(48.6%) had family history of diabetes, 1338(66.9%) were living in urban areas, 1068(53.4%) were university graduates, 804(40.2%) were employed and 1152(57.6%) belonged to socio-economically balanced families. Composite knowledge score was significantly associated with age and socio-economic status (p<0.05). A highly significant association was observed regarding family history (p<0.001), level of education (p<0.0001) and occupation (p<0.001) with composite knowledge score. Conclusion: The knowledge level about diabetes was seen to be average. Key Words: Complications of diabetes mellitus, Diabetes knowledge, Management of diabetes mellitus, Pakistani population, Questionnaire. Continuous...